Development and instrument validation of Indonesian achievement motivation scale using the Rasch model - Wiyono, Bambang Dibyo; Hidayah, Nur; Ramli, Muhammad; Atmoko, Adi; Shafie, Amin Al-Haadi (Institute of Advanced Engineering and Science, 2025)
This research involves the development of items on an achievement motivation scale that is used in improving the achievement motivation of senior high school students. No research on instrument development has been carried out on measuring the level of achievement motivation of senior high school students in Indonesia. Participants tested the development of 38 items and consisted of 1,909 respondents as students from senior high schools in the City of Surabaya. The utilized analysis technique was the Rasch model. Results of applying the Rasch analysis indicated that achievement motivation scale was good, proper, and appropriate in items to the model. The accomplishment motivation scale is a valid and dependable instrument for precisely determining pupils’ levels of accomplishment motivation. In light of the achievement motivation scale results, this study explores the consequences and suggests directions for future research on the use of guidance and counseling.